Deprecjonowanie wyznania religijnego w dyskusjach między katolikami a protestantami - dziedziny wartościowania = Depreciation of the religious denomination in discussions between Catholics and Protestants - fields of valorisation - Cieśla, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to review the areas of valuation that can be seen in discussions between Catholics and Protestants on the Internet. The analyzed texts were published under the films whose authors (lay and clergy) explain the differences between the two faiths.
Keywords: wartościowanie; katolicyzm; protestantyzm; dyskurs internetowy; komentarz internetowy; valorisation; Catholicism; Protestantism; Internet discourse; Internet commentary